Burnout syndrome in medical professionals with activities in COVID-19 ICU in Teresina/ PI (Research, Society and Development, 2021)
Objective: to verify the prevalence of burnout syndrome during the COVID-19 pandemic among physicians who worked in ICUs (Intensive Care Units). Methodology: This is a cross-sectional observational epidemiological study, with a quantitative approach, descriptive in nature, of a basic nature. The data used were acquired through a questionnaire carried out on the Google Forms platform. Results: 42 doctors participated, 25 men and 17 women. 85.7% of the participants had been working for more than two years. Only 12 professionals performed another profession. Indicative of Burnout was found in 57.1% of physicians. Conclusion: it is suggestive that a significant number of positive cases of Burnout Syndrome occurred, requiring attention to the mental well-being of health workers not only during the COVID-19 pandemic, but also in future pandemic situations. Such care is important to provide quality and more humanitarian care for patients cared for by professionals and for their protection.